Wonder Woman (2017): A World War II movie set in World War I - Machado, José Otaviano da Mata (2020)
Wonder Woman, a 2017 movie adaptation directed by Patty Jenkins, offers a contemporary look into the First World War. However, the comic books by which the adaptation was inspired are products of the so-called “Golden Age” of American super-hero comic books, and are notably a product of the Second World War. Therefore, the adaptation effects a process of chronological displacement of Wonder Woman’s traditional setting. Such displacement has direct effects on how the work is perceived – effects caused, in great part, by the profound differences between the myths of each of the two World Wars (HYNES, 1992, 1998). The present work investigates the effects of this displacement, and its consequences for a contemporary look on the First World War.